2001
DOI: 10.1002/1096-8628(20010115)98:2<191::aid-ajmg1030>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Behavior phenotype in the RSH/Smith-Lemli-Opitz syndrome

Abstract: The behavior phenotype of Smith-Lemli-Opitz syndrome (SLOS) was studied by assessing behavior, social, and communication abilities, sensory hyperreactivity, and the deficits associated with autistic disorder. Fifty-six SLOS subjects, age 0.3 to 32.3 years, were evaluated by multiple age-dependent questionnaires and telephone interviews. Of the 56 subjects, 50 (89%) had a history of repeated self-injury: 30 (54%) bit themselves; 27 (48%) head-banged; and 30 (54%) threw themselves backward in a highly characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
126
2
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(138 citation statements)
references
References 31 publications
7
126
2
3
Order By: Relevance
“…The incidence has been estimated to be one in 10 000 to one in 60 000. 65 SLO can be improved by supplementary dietarial cholesterol. The phenotype is variable with only rare symptoms or multiple congenital anomalies comprising cleft palate, cataracts, ptosis, hypospadias, syndactyly and a distinctive craniofacial appearance.…”
Section: Single Gene Disorders Associated With Admentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence has been estimated to be one in 10 000 to one in 60 000. 65 SLO can be improved by supplementary dietarial cholesterol. The phenotype is variable with only rare symptoms or multiple congenital anomalies comprising cleft palate, cataracts, ptosis, hypospadias, syndactyly and a distinctive craniofacial appearance.…”
Section: Single Gene Disorders Associated With Admentioning
confidence: 99%
“…66 The most common malformation in large-scale studies was the syndactyly of toes 2 and 3; however, only present in about 80% of affected individuals. 66,67 Two studies have shown a high rate of AD in individuals with SLO, 65,68 especially in children with a start of cholesterol supplementation after age 5 years.…”
Section: Single Gene Disorders Associated With Admentioning
confidence: 99%
“…[282][283][284] Interestingly, SLOS is a neurodevelopmental disorder characterized by high rates of autism. 285,286 The disease is caused by mutations in DHCR7, leading to a disruption in cholesterol synthesis and an accumulation of precursor sterols. 287 In mice, the loss of Dhcr7 function results in severe respiratory impairment, failure to feed, and death soon after birth.…”
Section: Genes Responsive To Environmental Factorsmentioning
confidence: 99%
“…
AbstractAlthough Smith-Lemli-Opitz Syndrome (SLOS), a genetic condition of impaired cholesterol biosynthesis, is associated with autism [Tierney et al, 2001], the incidence of SLOS and other sterol disorders among individuals with autism spectrum disorders (ASD) is unknown. This study investigated 1) the incidence of biochemically diagnosed SLOS in blood samples from a cohort of subjects with ASD from families in which more than one individual had ASD and 2) the type and incidence of other sterol disorders in the same group.
…”
mentioning
confidence: 99%
“…Most SLOS individuals who survive the newborn period are compound heterozygotes for a common DHCR7 null mutation and a milder missense mutation, whereas the most mildly affected SLOS individuals carry two missense alleles with residual DHCR7 activity. Various genetic disorders such as fragile X syndrome, Joubert syndrome, Prader-Willi syndrome, tuberous sclerosis, and Down syndrome may present with autism spectrum disorders [Folstein and Piven, 1991].Individuals with SLOS children have a high incidence of autism [Tierney et al, 2001]. Among 17 patients with SLOS administered the algorithm questions of the Autism Diagnostic Interview-Revised (ADI-R; Lord et al, 1994), 53% met criteria for autism.…”
mentioning
confidence: 99%